Family Structure Patterns from Childhood through Adolescence and the Timing of Cohabitation among Diverse Groups of Young Adult Women and Men - Johnston, Carol A. (Dev Psychol, 2019)
Family structure changes experienced by children are likely to shape their transitions into young adulthood, including the formation of their own romantic relationships. This study examined links between children’s family structure trajectories from childhood through adolescence and their timing of entry into cohabitation as young adults, a transition with implications for future relationship instability through adulthood. Repeated measures latent class analysis identified configurations of family structures and family structure changes from birth through age 15 among 10,706 young people in the National Longitudinal Survey of Youth 1979 Child and Young Adult Surveys. A Cox proportional hazard model then used the resulting classes to predict timing into cohabitation over the period from age 15 to age 38. Both timing of family structure transitions and the type of transitions (e.g., early transitioning into a stepfamily home) were associated with earlier entry into cohabitation. Notably, links between family structure trajectories and the timing of cohabitation differed by gender and race/ethnicity (Latinx, African-American, White), such as a faster entry into cohabitation by women who experienced early entry into stepfamily structures. Regardless of gender, Latinx and White young adults were faster to enter into cohabitation if they lived in a stepfamily structure during early childhood.